High resolution study of the strongly interacting v3(F2)/v1(A1) bands of 28SiD4; High Resolution Molecular Spectroscopy, HRMS 2018 - Raspopova N. I. Natalya Ivanovna; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Bauerekker Z. Zigurd; Sydow C. Christian; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich (2018, 2018)
Title screen